Constitutional questions and citizens' rights an omnibus comprising : Constitutional questions in India, the president, parliament and the states and Citizens' rights judges and state accountability - Noorani, Abdul Gafoor Abdul Majeed, 1930-; Noorani, Abdul Gafoor Abdul Majeed, 1930-; Noorani, Abdul Gafoor Abdul Majeed, 1930- (New Delhi ; Oxford : Oxford University Press, 2006)
Bringing together two collections of essays, this volume is thematically organized across sections on the president, parliament, states, judiciary, elections, commissions of enquiry, the civil service, the right to information, armed forces and the political process in India. It covers the politically tumultuous years between 1989 and 1999.
Description based on print version record.
Includes bibliographical references.
Keywords: Constitutional law -- India; Judicial power -- India; Government liability -- India; Civil rights -- India; India -- Politics and government